Applicability of ohmic heating assisted vacuum evaporation for concentration of sour cherry juice. (November 2017) - Sabanci, Serdal; Icier, Filiz
Abstract: Sour cherry juice having total soluble solids (TSS) of 19.2% was evaporated up to 65% TSS at vacuum (gauge pressure of 580 mm-Hg) by applying ohmic heating at three different voltage gradients (10–14 V/cm). Total process times were determined as 40, 55, 75, and 85 min for 14 V/cm, 12 V/cm, and 10 V/cm, and vacuum evaporation (VE), respectively. The change of moisture content during ohmic assisted vacuum evaporation and VE processes were investigated by seven different empirical models. The best fitting model was Midilli model for three different voltage gradients and VE. The electrical conductivity values at different voltage gradients varied between 0.41 and 1.13 S/m for different TSS contents. The changes of EC values were examined in detail for three different regions; heating up period, first evaporation period, and second evaporation period. EC increased until a critical % TSS content (32% TSS), then remained constant for certain time (until 45% TSS) depending on voltage gradient, and then it had tendency to decrease. Ohmic heat generation increased sharply during heating period, then decreased dramatically during evaporation periods. It is recommended that ohmic heating could be alternatively used as the heat source to shorten the process times of vacuum evaporation applied for concentration of fruit juices. Highlights: Ohmic heating was successfully integrated to vacuum evaporation system. OVE applied at 14 V/cm decreased the process time to the half compared to VE. Change of EC was investigated in three different periods during evaporation. EC increased until critical TSS content, and then decreased. Heat generation rate increased sharply during heating, and then decreased during evaporation.